APAKAH GAYA HIDUP, KEMUDAHAAN PENGGUNAAN, DAN KEAMANAN TERHADAP KEPUTUSAN PENGGUNAAN MOBILE BANKING PADA GENERASI Z: BUKTI EMPIRIS MAHASISWA IAIN PALOPO - esya, bunga (Dinamis : Journal of Islamic Management and Bussiness, 2023)
This study aims to determine the effect of lifestyle, ease of use, and security on the decision to use mobile banking in Generation Z. In the digital era like today the behavior of generation to generation has changed a lot, especially in terms of conducting banking transactions, which prioritizes aspects of ease of use, security and according to the lifestyle of gen Z in today's digital era. The convenience of mobile banking transaction services is able to change lifestyles, especially among students. This research method is quantitative with a descriptive approach. The data collection technique in this study used a questionnaire, which was distributed online to FEBI students, with a total population of 2,430 students of the Faculty of Economics and Islamic Business at IAIN Palopo. The sample used with the Slovin technique formula was 99 students. The data analysis technique used is data analysis test, classical assumption test and hypothesis testing. The results of this study indicate that, the lifestyle variable (X1) partially has a significant and positive effect on the decision to use mobile banking in generation Z. This can be seen from the Thitung value of X1. This can be seen that the value of Tcount> Ttable. Then the ease of use variable (X2) partially has a significant and positive effect on the decision to use mobile banking. This can be seen that the value of Tcount> Ttable. And the security variable has a significant and positive effect on the decision to use mobile banking in generation Z. This can be seen that the value of Tcount> Ttable. Finally, the lifestyle, ease of use and security variables simultaneously have a significant and positive effect on the decision to use mobile banking in generation Z. This can be seen that Fcount> Ttable. So it can be concluded that Ha is accepted and Ho is rejected.